Cross Sectional Evaluation of Females in Fatal Road Traffic Deaths - M.Venkatesan; Shaan Raj; U.Jagdish Kamal Chander; Priyadarshee Pradhan; P.Sampath Kumar; Sathya Jagdish (Indian Journal of Forensic Medicine & Toxicology, 2021)
The unnatural deaths can be divided as per the manner as suicidal, accidental, homicidal or undetermined.the accidental deaths constitute a major portions of unnatural deaths. Female population in India were oftennot acquainted to travel by their own like by means of two wheelers and four wheelers in olden days but theproportion has a gradual rise in recent times. The total number of 107 cases constituted unnatural femaledeaths autopsied from June 2013 to August 2014 out of which 52 cases were confirmed to be road trafficdeaths constituting 49% out of which 10 were pedestrians 33 travelled in two wheeler and 9 in four wheeler.On analysis of these 33 cases it was observred that most of them were pillion riders (73%), 95% of femalevictims did not use helmet when travelled on two wheeler and the injuries on the body were more on the leftside (69%) than right. All the victims who travelled in the four wheeler did not use seat belt(9)